Endeavour. The complete fourth season [videorecording (DVD)] - Evans, Shaun, 1980-; Allam, Roger; Lesser, Anton (Masterpiece theatre (Television program), 2017)
Following the finale of Season three, Oxford's finest are picking up the pieces of their personal and professional lives. DC Endeavour Morse awaits the result of his Sergeant's Exam, while DI Fred Thursday and his wife Win struggle to cope with their children flying the nest. With Sam gone to the Army and the traumatized Joan gone off to who knows where, there are even greater challenges still to face.